Gene mutational profile of BRCAness and clinical implication in predicting response to platinum-based chemotherapy in patients with intrahepatic cholangiocarcinoma. (August 2022) - Rimini, Margherita; Macarulla, Teresa; Burgio, Valentina; Lonardi, Sara; Niger, Monica; Scartozzi, Mario; Rapposelli, Ilario G.; Aprile, Giuseppe; Ratti, Francesca; Pedica, Federica; Verdaguer, Helena; Nappo, Floriana; et al.
Abstract: Background and Aims: Biliary tract cancers are rare malignancies with a poor prognosis and scarce therapeutic strategies. The significance of BRCAness in this setting is already unknown. Method: Tissue specimens of BTC patients treated with platinum-based chemotherapy have been analyzed through the FOUNDATIONPne assay. Results: 72/150 (48%) BRCAness mutated and 78/150 (52.0%) wild type (WT) patients were included. The most commonly mutated genes in the BRCAness mutated group were: ARID1A (N = 32, 44%), CDKN2A (N = 23, 32%), KRAS/NRAS (N = 16, 22%), CDKN2B (N = 13, 18%), BRCA2 (N = 13, 18%), PBRM1 (N = 12, 17%), ATM (N = 11, 15%), FGFR2 (N = 10, 14%), TP53 (N = 8, 11%), IRS2 (N = 7, 10%), CREBBP (N = 7, 10%) (table 3, figure 1). At the univariate analysis BRCAness mutation was associated with longer median Progression Free Survival (mPFS) (HR 0.68; 95% CI 0.49-0.95; p = 0.0254); it was not associated with longer mOS but a trend toward a benefit in survival was found (HR 0.77; 95% CI 0.50-1.19; p = 0.2388). Patients with BRCAness mutation showed a higher percentage of disease control rate (77.8 vs 67.9; p = 0.04) compared to patients WT. Multivariate analysis confirmed BRCAness mutation (HR 0.66; 95% CI: 0.45-0.98; p = 0.0422) as independent favorable prognostic factors for PFS and a positive trend was found for OS (HR 0.84; 95% CI: 0.53-1.33; p = 0.3652). Conclusion: BRCAness BTC patients showed a better PFS compared BRCAnessWT patients after exposure to platinum-based chemotherapy. Moreover, the OS curves' trend showed in our analysis suggests that BRCAness mutated patients could benefit from a maintenance therapy with PARPi. Highlights: The role of altered DNA damage repair pathways in BTC setting is already unknown. We conducted a retrospective analysis on BTC patients treated with platinum salts. BRCAness phenotype is an independent favourable prognostic factor for PFS. BRCAness BTC patients seem to be more sensitive to platinum compounds. Sequential strategies of platinum salts and PARP inhibitors should be tested.